2021
DOI: 10.1021/acssuschemeng.1c04452
|View full text |Cite
|
Sign up to set email alerts
|

Selective Decarbonylation of Fatty Acids to Long-Chain Alkenes via PtSn/SnOx-Induced C–O Activation

Abstract: Long-chain olefins are an important class of chemicals and platform intermediates. A green and promising route for synthesizing long-chain olefins is the one-step decarbonylation and dehydration of biomass-derived fatty acids under hydrogen-free conditions. Major impediments for synthesizing olefins from fatty acids are (1) the difficulty in selectively cleaving C–O bonds (461.5 kJ/mol) of fatty acids and (2) the tendency to break the weaker C–C bonds (384.9 kJ/mol) to generate alkanes. Traditional homogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In 2021, Zhao et al reported the preparation of 1-heptadecene in a 73% yield from stearic acid without any exogenous hydrogen under optimized conditions (320 °C, 4 h). The bimetallic PtSn/SiO 2 catalyst influenced FFA adsorption on the SnO x sites via the acyl group for selective decarbonylation . FAEs can be catalytically decarbonylated into long-chain alkenes, where the alcohol byproduct is recycled to form more starting material …”
Section: Decarbonylation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Zhao et al reported the preparation of 1-heptadecene in a 73% yield from stearic acid without any exogenous hydrogen under optimized conditions (320 °C, 4 h). The bimetallic PtSn/SiO 2 catalyst influenced FFA adsorption on the SnO x sites via the acyl group for selective decarbonylation . FAEs can be catalytically decarbonylated into long-chain alkenes, where the alcohol byproduct is recycled to form more starting material …”
Section: Decarbonylation Reactionsmentioning
confidence: 99%
“…The bimetallic PtSn/SiO 2 catalyst influenced FFA adsorption on the SnO x sites via the acyl group for selective decarbonylation. 130 FAEs can be catalytically decarbonylated into long-chain alkenes, where the alcohol byproduct is recycled to form more starting material. 131…”
Section: Dehydration Reactionsmentioning
confidence: 99%
“…The production of long-chain olefins from fatty acids over supported catalysts has been widely reported, but the selective conversion to C 2 –C 4 olefins has rarely been explored. 19…”
Section: Introductionmentioning
confidence: 99%
“…The production of long-chain olefins from fatty acids over supported catalysts has been widely reported, but the selective conversion to C 2 -C 4 olefins has rarely been explored. 19 In general, upgrading of triglycerides is accomplished by subsequent catalytic cracking and deoxygenation to reduce the chain length. 20 The conversion of fatty acids into olefins involves several reaction steps, like hydrodeoxygenation, decarboxylation, catalytic cracking or dehydrogenation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation